Financial Analysis of Dalbavancin for Acute Bacterial Skin and Skin Structure Infections for Self-Pay Patients - Pizzuti, Adam G. (Infect Dis Ther, 2020)
INTRODUCTION: Acute bacterial skin and skin structure infections (ABSSSI) are an increasing cause of admission in the self-pay population. We previously reported that patients with ABSSSI discharged to receive dalbavancin showed a decreased length of stay (LOS) and total direct costs without increasing 30-day readmission rate. For patients who are financially eligible, a dalbavancin vial replacement program can offset costs. The objective of this study was to determine cost differences in treating ABSSSI in self-pay inpatients discharged to receive dalbavancin compared to standard of care (SOC). METHODS: This retrospective cohort within a community health system compared self-pay adult inpatients with ABSSSI from February 3, 2016 to August 5, 2019 discharged to receive dalbavancin at an outpatient infusion center with SOC intravenous antibiotics. Patients were included with cellulitis, abscess, or postoperative wound infections diagnoses on the basis of International Classification of Disease, Tenth Revision (ICD-10) codes. Excluded populations were patients without dalbavancin vial replacement performed, pregnant, infections caused exclusively by gram-negative bacteria or fungi, or ICD-10 codes not consistent with ABSSSI. The primary outcome was direct cost of hospital stay. Secondary outcomes included length of stay (LOS), 30-day readmission rates, adverse events (AE), and indirect hospital costs. On the basis of previous studies, a one-sided Student’s t test was performed on financial data. RESULTS: Twelve dalbavancin and 263 SOC patients met inclusion criteria. Direct cost ($2758 vs $4010, p = 0.105) and indirect hospital cost ($2913 vs $3646 , p = 0.162) per patient were less in the dalbavancin group. There was no significant difference between median LOS (4 vs 4, p = 0.888), AE (0% vs 14.8%), and 30-day readmission rates for dalbavancin vs SOC group (8.3% vs 7.2%, p = 0.604). CONCLUSION: Self-pay patients with ABSSSI discharged to receive dalbavancin with vial replacement resulted in decreased direct and indirect costs per patient with similar 30-day readmission rates, AE, and LOS. More studies targeted toward this population are warranted to determine ultimate benefit.